Kebebasan intelektual di perpustakaan - Fatmi Sarah (UIN Sumatera Utara, 2015)
This paper discusses about intellectual freedom in library, Freedom to acquire and use information in the library is one important element in intellectual freedom in library. Each user is in the library is entitled to use any form of collections and information in the library without the obstacles of any party.Rights of intellectual freedom in seeking and obtaining user information in the library is one of the fundamental right to freedom intellectual although the information sought by the user is an issue or a subject that is quite sensitive and dangerous. However, librarians sought to meet the needs of such users because the library is a democratic and neutral space where each user can library obtain all the information they need without fear and discrimination